Vận dụng lí thuyết giáo dục toán thực (RME) trong dạy học nội dung “Khoảng tin cậy cho tỉ lệ”: Một nghiên cứu theo thiết kế bán thực nghiệm - Đào Hồng Nam, Đào Hồng Nam (Tạp chí Giáo dục, 2026)
In teaching inferentialstatistics at the university level, the topic of confidence intervalsfor proportionsis often presented with an overemphasis on formulas and procedural steps, which limits students’ conceptual understanding. In response, this study aims to evaluate the effectiveness of applying Realistic Mathematics Education (RME) in teaching this topic through a quasiexperimental design. The quantitative results indicate that the experimental group significantly outperformed the control group, with a statistically significant difference (p < 0.001) and a large effect size (r = 0.61). Notably, analysis of students’ written responses shows that they were not only able to identify the conditions for applying the Wald confidence interval but also recognized its limitations when the estimated bounds fall outside the interval [0, 1]. Consequently, they actively adopted alternative methods such as Wilson or Clopper - Pearson to produce more realistic and appropriate conclusions. These findings suggest that the application of RME contributes positively to improving teaching effectiveness by linking statistical reasoning to meaningful real-world contexts.